Angola's uncertain transition. Issue 10 (26th November 2017) - Unknown
Abstract : An improbably smooth transition in Angola appears to be taking shape under President João Lourenço, inaugurated on 26 September. But he faces major challenges in diversifying Angola's plummeting economy so as to make it less dependent on oil, and in rehabilitating its international reputation, which has been damaged by longstanding corruption. Much depends on whether he can exploit his non-partisan instincts and common touch to become a charismatic leader with a long-term vision.